2021
DOI: 10.1042/bst20200466
|View full text |Cite
|
Sign up to set email alerts
|

The structure and function of protein kinase C-related kinases (PRKs)

Abstract: The protein kinase C-related kinase (PRK) family of serine/threonine kinases, PRK1, PRK2 and PRK3, are effectors for the Rho family small G proteins. An array of studies have linked these kinases to multiple signalling pathways and physiological roles, but while PRK1 is relatively well-characterized, the entire PRK family remains understudied. Here, we provide a holistic overview of the structure and function of PRKs and describe the molecular events that govern activation and autoregulation of catalytic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 162 publications
(216 reference statements)
0
5
0
Order By: Relevance
“…PKN may inhibit insulin signalling by directly interacting with PDK1 and Akt 29 . A previous study showed that PKN2 contributes to cell adhesion‐mediated activation of Akt 30 . Moreover, phosphoproteomics analysis of PKN2−/− mouse embryonic fibroblasts revealed that Akt pathway activity is increased in these cells 31 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PKN may inhibit insulin signalling by directly interacting with PDK1 and Akt 29 . A previous study showed that PKN2 contributes to cell adhesion‐mediated activation of Akt 30 . Moreover, phosphoproteomics analysis of PKN2−/− mouse embryonic fibroblasts revealed that Akt pathway activity is increased in these cells 31 .…”
Section: Discussionmentioning
confidence: 98%
“… 29 A previous study showed that PKN2 contributes to cell adhesion‐mediated activation of Akt. 30 Moreover, phosphoproteomics analysis of PKN2−/− mouse embryonic fibroblasts revealed that Akt pathway activity is increased in these cells. 31 Furthermore, PKN2 knockdown impairs insulin‐responsive glucose metabolism and unexpectedly activates 5′‐adenosine monophosphate‐activated protein kinase, exerting downstream effects on lipid and protein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PKs also play roles in the immune response and nervous system function [ 60 ]. Among the protein kinases,, serine/threonine-protein kinases (STPKs) are the most extensively studied and include cyclin-dependent kinase (CDK), mitogen-activated protein kinase (MAPK), DNA-dependent protein kinase, natto kinase, and protein kinase C [ 61 ]. In our study, many genes encoding STPK were significantly regulated in P .…”
Section: Discussionmentioning
confidence: 99%
“…These processes include cytoskeletal regulation, cell adhesion, apoptosis, regulation of meiotic maturation and signaling to the cell nucleus, and tumorigenesis. 14 …”
Section: Introductionmentioning
confidence: 99%
“…These processes include cytoskeletal regulation, cell adhesion, apoptosis, regulation of meiotic maturation and signaling to the cell nucleus, and tumorigenesis. 14 Another factor that may affect cell cycle progression and is affected by ionizing irradiation is transforming growth factorβ (TGF-β) which regulates a wide range of biological processes, including cell growth, differentiation, apoptosis, motility, immune regulation, cell invasion, and cell cycle regulation by blocking progress through the G1 phase. 15 On the other hand, the effect of TGF-β is dependent on the physiological environment.…”
Section: Introductionmentioning
confidence: 99%